Aquaman. Volume 3, Throne of Atlantis - Johns, Geoff, 1973- (New 52 Aquaman, 2013)
"Atlantis attacks! Aquaman, long having since severed ties with his people, watches as as armies rise from the water and attack the surface world. The Justice League--Superman, Batman, Wonder Woman, the Flash and Cyborg--answer the call, defending the shores from the invading Atlantean hordes. But whose side is Aquaman on? With his brother Orm at the head of the undersea army, will Aquman choose to side with his Earth-bound superteam? Or his own people?"--Amazon.com.